The Influence of Women in Political Leadership in Malaysia: Implications for Governance and Social Sustainability (Architecture Image Studies, 2025)
This study explores the impact of women’s participation in political leadership in Malaysia and its implications for governance and social sustainability. Despite women comprising nearly half of the population and registered voters, their representation in politics remains limited, falling short of the 30% target outlined in national and international commitments. Using a qualitative approach, the study collected primary data through interviews with politicians, academics, and NGO representatives, complemented by secondary data from official documents, policy reports, academic publications, and media sources. The findings show that women’s involvement enhances transparency, integrity, and accountability in governance. Additionally, women broaden policy priorities by addressing social issues such as family welfare, mental health, and the rights of vulnerable groups, which are often overlooked in traditional policymaking. However, cultural patriarchy, internal party barriers, and the lack of legally mandated gender quotas remain significant challenges. To address these, the study recommends legal enforcement of a 30% gender quota, expansion of leadership development programs for women, and improved institutional support. These measures aim to ensure more balanced and effective political participation by women. The study’s findings are expected to support the development of inclusive policies and strengthen democratic governance in Malaysia.